Pemetaan dan Rekomendasi Papan Reklame Tetap berbasis WebGIS: Studi Kasus Jade Indopratama - Dennie Novandhika; Fatwa Ramdani; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Malang City has many fixed billboard locations for rent. Noted there are more than 100 permanent billboards scattered in the city of Malang. Based on the distribution, there was a problem related to the information that the billboards had provided. Potential advertisers are not easy to get information about the distribution point of the billboard location. This problem occurs because there is no WebGIS that displays fixed billboard maps. Therefore there is a need for WebGIS mapping and permanent billboard recommendations to overcome this problem. WebGIS mapping and billboard recommendations are still being built using agile development methods. Billboard recommendations on WebGIS are determined using Tsukamoto's fuzzy calculation formula. WebGIS, which was completed, produced an interface consisting of narration and digital maps. Digital maps on WebGIS include markers, search features, filter features, specification information, photos, and photosphere from billboards. WebGIS is tested using the usability and compatibility parameters. Based on the usability test results, WebGIS can be said to be excellent or can be used easily. Based on compatibility test results, WebGIS can be said to be compatible in several browsers such as Edge, Opera, Chrome, iOS, and Android. WebGIS that has been built and tested is expected to be useful for all users.